The Inclusion of Sociolinguistic Context in the Text Materials of English Text Books for Junior High School - Endang Susilawati (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This research is conducted for two main objectives, (1) to identify whether the sociolinguistic contexts have been included in the presentation of interpersonal and transactional text materials in the selected textbook; (2) to analyze the variables of contexts that might have been included. The text book being analysed is an English textbook for Grade VII, “The title is Bahasa Inggris When English Rings a Bell, SMP/MTs Kelas VII, which is written by Siti Wachidah, Asep Gunawan, Diyantari, Yuli Rulani Khatimah. It is reviewed and edited by Rd. Safrina Noorman and Lestari Manggong and published in 2017 by Pusat Kurikulum dan Perbukuan, Balitbang, Kemendikbud. This research is an evaluation research by applying content analysis method. The analysis is started by (1) identifying or codifying the text materials which belong to both interactional and transactional conversation; (2) categorizing the types of conversations (interactional or transactional); (3) analyzing the inclusion of sociolinguistic contexts in each of the conversations based on the four out of five variables of sociolinguistic contexts proposed by Harmer (2001). The variables include setting, participant, channel, and topic; the last (4)interpreting the result of analysis. The findings show that almost all the topics of the dialog texts have been designed concurrently with the English syllabus for SMP/MTs Kelas VII. Yet, there are only few variables of setting, participant, and channel which are identifiable. To conclude, the variables of sociolinguistic contexts have not been entirely included in the text materials.